Majas dan Citraan dalam Kumpulan Puisi Blues Untuk Bonnie Karya W.S. Rendra dan Pemakaiannya - zuniar kamaluddin mabruri; sri dwi ratnasari (Universitas Aki, 2015)
This research aims to: (1) describe the use of figure of speech and the meaning form in a collection of poems Blues for Bonnie by WS Renda. (2) describe the form of the use of imagery and poetry in the set of meanings Blues for Bonnie by WS Renda. Techniques of data collection were done by using libraries, observation, and record. Data are in the form of words, phrases, and sentences in a collection of poems Blues for Bonnie by WS Renda. Sources of data in this study are primary data source in the form of five poems Blues for Bonnie published by Peacock Press, East Jakarta in 2008 and secondary data sources include journals, papers, and articles. Data analysis techniques in this study use a model of Riffatere semiotic readings (heuristic and hermeneutic reading). The results indicate that there are utilization of figure of speech and imagery in a collection of poems Blues for Bonnie by WS Rendra. Figure consists of (a) figure of speech metaphor, (b) figure of speech simile, (c) figure of speech personification, (d) figure of speech metonemia, and (e) sinedoki figure of speech. Figure of speech meaning and imagery in a collection of poems by WS Blues for Bonnie Renda is divided into two, namely (a) the meaning of figure of speech and (b) the meaning of the images in a collection of poems Blues for Bonnie by WS Renda. Figure of speech meaning covering, the social aspects of which moral deviation problem, the problem of poverty, politics, and religious aspects. As for the meaning of speech image includes, among others the social aspects of moral aberration problem, the problem of poverty, political, and religious aspects. Keywords: figure of speech, imagery, poetry Blues for Bonnie, study stylistics